Weak ferromagnetism and superparamagnetic clusters coexistence in YFe1−xCoxO3 (0 ≤ x ≤ 1) perovskites. (October 2017) - Pomiro, Fernando; Gil, Diego M.; Nassif, Vivian; Paesano, Andrea; Gómez, María I.; Guimpel, Julio; Sánchez, Rodolfo D.; Carbonio, Raúl E.
Graphical abstract: Highlights: Synthesis, structural and magnetic characterization of the YFe1-x Cox O3 (x = 0, 0.3, 0.5, 0.7 and 1) perovskite series. Weak Ferromagnetism and Superparamagnetic clusters coexistence. Co 3+ ions in different spin configurations states (LS, IS and HS). Phase diagram of the magnetic properties of the YFe1-x Cox O3 solid solutions as composition changes. Abstract: YFe1-x Cox O3 (x = 0, 0.3, 0.5, 0.7 and 1) perovskite solid solutions were synthesized by thermal decomposition of the cyano-metal complexes Y[Fe1-x Cox (CN)6 ]·4H2 O. All perovskites belong to the orthorhombic Pnma space group. Mössbauer spectra at room temperature show that samples with low Co 3+ content are magnetically ordered, while samples with high Co 3+ content are paramagnetic. A clear decrease of the magnetic order temperature was observed by magnetization vs. temperature experiments. At high temperatures, YFe0.3 Co0.7 O3 is paramagnetic and a non common increase of magnetization is observed. The later can be related to the thermal excitation of Co 3+ in low spin (LS) configuration to intermediate (IS) or high spin (HS) configuration. Along the different compositions of YFe1-x Cox O3 solid solutions there is a competition between weak ferromagnetism (WFM) and superparamagnetic (SPM) clusters. WFM due to Fe 3+ cations prevail in rich Fe 3+ samples (x = 0 and 0.3) and the Fe 3+ cations that form SMP clusters prevail in the sample with x = 0.7. Besides, in the sample with x = 0.5 we postulate a slight prevalence of WFM due to Fe 3+ cations. For YFe1-x Cox O3 with x = 0.3, 0.5 and 0.7 neutron powder data at 2, 150 and 350 K were refined with the irreducible representation Γ4 (Ax Fy Gz ) .